2014
DOI: 10.1002/ijop.12128
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the implications of social change for human development: Perspectives, issues and future directions

Abstract: Researchers have investigated the implications of social change for human development from different perspectives. The studies published in this special section were conducted within Greenfield's theoretical framework (2009). The findings concerning links between specific sociodemographic features (e.g., commercial activities, schooling) and individual cognition and social behaviour are particularly interesting because they tap the underlying forces that drive human development. To further understand the issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 21 publications
5
45
0
Order By: Relevance
“…For better or worse, globalization is an influential context for adolescent development in the 21st century (Chen, 2015;Jensen & Arnett, 2012). Western culture and media have played a particularly prominent role in social change (e.g., toward western individualistic norms; see Greenfield, 2009) and nutritional change (e.g., toward a western diet high in fat, sugar, and salt; Popkin, Adair, & Ng, 2012), especially in the majority world (i.e., developing countries).…”
mentioning
confidence: 99%
“…For better or worse, globalization is an influential context for adolescent development in the 21st century (Chen, 2015;Jensen & Arnett, 2012). Western culture and media have played a particularly prominent role in social change (e.g., toward western individualistic norms; see Greenfield, 2009) and nutritional change (e.g., toward a western diet high in fat, sugar, and salt; Popkin, Adair, & Ng, 2012), especially in the majority world (i.e., developing countries).…”
mentioning
confidence: 99%
“…The changes in sociodemographic features and value systems inevitably affect social perceptions of children’s behaviors. Researchers (e.g., Chen, 2015; Kağıtçıbaşı, 2012) have also suggested that ongoing urbanization and related social changes in many traditionally agricultural societies may lead to the integration of diverse, and perhaps conflictual, values. The integrated values in turn may enhance appreciation of, and positive attitudes toward, autonomous-related qualities and other mixed self- and group-oriented behaviors.…”
Section: Cultural Meanings Of Human Behaviors: Major Views and Issuesmentioning
confidence: 99%
“…The example most often used in the literature is the breakdown of the communist system in Eastern Europe and the Soviet Union (e.g., Kollontai, 1999; Pinquart et al, 2009; Round and Williams, 2010; Walker and Stephenson, 2010; Chen, 2015). For example, when Pinquart et al (2004, p. 341) introduced their research on social change, they made a distinction between “gradual” change, such as ideological change in many Western societies, and “abrupt social change,” which represents a form of social change that may be spurred by a sudden, dramatic transformation of economic, political, and social institutions.…”
Section: Constructing a Typology Of Social Change: The Characteristicmentioning
confidence: 99%